Global, regional, and national burden of myocarditis and its attributable risk factors in 204 countries and territories from 1990 to 2021: updated systematic analysis - Jiajia Ren; Wanyuan Liu; Xuting Jin; Chuchu Zhang; Xi Xu; Guorong Deng; Xiaoming Gao; Jiamei Li; Ruohan Li; Xiaoling Zhang; Yanli Hou; Gang Wang; et al. (Frontiers in Public Health)
BackgroundComprehending the current epidemiological trends and risk factors of myocarditis is crucial for guiding future targeted prevention and treatment strategies.MethodsUtilizing data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021, we conducted a secondary analysis of the incidence, prevalence, death, and disability-adjusted life years (DALYs) of myocarditis by sex, age group and socio-demographic index (SDI) across 204 countries and territories from 1990 to 2021. And non-optimal temperatures, defined as same-day exposure to ambient temperatures deviating from the minimum death risk threshold, were identified as risk-factors for myocarditis-related death and DALYs.ResultsFrom 1990 to 2021, the global prevalence of myocarditis increased from 320,623 (95% uncertainty interval: 268,557 to 371,912) to 505,030 (432,295 to 587,819). Concurrently, the age-standardized prevalence rate (ASPR) per 100,000 people also saw a slight increase (no statistical significance) from 6.35 (5.37 to 7.36) to 6.41 (5.48 to 7.44). However, the age-standardized incidence rate (ASIR), age-standardized death rate (ASDR) and age-standardized DALY rate (ASYR) exhibited declines, with estimated annual percentage changes of −0.20 (−0.23 to −0.17), −1.37 (−1.81 to −0.92) and −1.71 (−1.95 to −1.46), respectively. SDI quintile analysis showed that the high SDI quintile had the highest ASIR and ASPR, while the middle and high-middle SDI quintiles exhibited the highest ASDR and ASYR. Furthermore, the burden of myocarditis was notably high among males and older adult populations. Non-optimal temperature, particularly low temperature, emerged as a key risk factor for myocarditis-related ASDR and ASYR.ConclusionAlthough the ASIR, ASDR and ASYR for myocarditis exhibited decreasing trends from 1990 to 2019, further efforts are needed to develop targeted public health strategies, especially for low SDI regions, males, and older adult populations.